Association of simultaneously measured four-limb blood pressures with cardiovascular function: a cross-sectional study. Issue 2 (December 2016) - Song, Xiaorui; Li, Gaoyang; Qiao, Aike; Chen, Zhihui
Abstract Background Simultaneous measurement of four-limb blood pressures can improve the accuracy of cardiovascular disease diagnosis. This study aims to investigate the association of simultaneously measured four-limb blood pressures with cardiovascular function as the non-invasive diagnostic method of cardiovascular disease in primary care. Methods 229 subjects (62 males, mean age, 63.50 ± 11.13 years; 167 females, mean age, 59.47 ± 7.33 years) were enrolled. Four-limb blood pressure measurements were simultaneously performed using a blood pressure and pulse monitor device in the supine position. Cardiac functional parameters were also measured by using a cardiac hemodynamic detector in the same position. Data were statistically analyzed with SPSS15.0. Results The mean age of the 229 subjects was 60.56 ± 8.68 years. Cardiovascular functional parameters decreased with age and body mass index (BMI), only the total peripheral resistance (TPR) was in contrast. Age, BMI, left ankle diastolic pressure (LADP), high arm mean arterial pressure (HARMAP), left arm diastolic pressure (LARDP) and right ankle diastolic pressure (RADP) were significantly correlated with cardiovascular functional parameters. Cardiovascular functional parameters have significant differences with inter-arm difference in systolic blood pressure (SBP) between ≥10 and <10 mmHg, inter-ankle difference in SBP between ≥15 and ≥20 mmHg, inter-ankle difference in SBP between ≥15 and <10 mmHg and right ankle brachial index (RABI) between ≤0.9 and ≥1.0. After excluding 99 hypertensive patients, a part of cardiovascular functional parameters has still significant differences with inter-arm difference in SBP between ≥10 and ≥15 mmHg and RABI between ≤0.9 and ≥1.0. Conclusion Age, BMI, LADP, HARMAP, LARDP and RADP were the determinants of cardiovascular functional parameters. In addition, a part of cardiovascular functional parameter is associated with inter-arm difference in SBP ≥10 mmHg, inter-ankle difference in SBP ≥15 mmHg and RABI ≤0.9, while these differences still existed after excluding 99 hypertensive patients. Hence, simultaneous measurement of four-limb blood pressures has become feasible and useful approach to the non-invasive diagnostic method of cardiovascular disease in primary care.